2022
DOI: 10.1186/s12987-022-00322-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression and functions of adenylyl cyclases in the CNS

Abstract: Adenylyl cyclases (ADCYs), by generating second messenger cAMP, play important roles in various cellular processes. Their expression, regulation and functions in the CNS, however, remain largely unknown. In this review, we first introduce the classification and structure of ADCYs, followed by a discussion of the regulation of mammalian ADCYs (ADCY1-10). Next, the expression and function of each mammalian ADCY isoform are summarized in a region/cell-specific manner. Furthermore, the effects of GPCR-ADCY signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 189 publications
(224 reference statements)
0
32
0
Order By: Relevance
“…ADCY1 and NPTX1 were also found to be associated with BD in our analysis as well as other GWAS studies 69,70 . ADCY1 plays a potential role in learning and memory 71,72 , whereas NPTX1 is required for neural cell speci cation and is also known to be involved in synaptic plasticity 73,74 .…”
Section: Discussionmentioning
confidence: 99%
“…ADCY1 and NPTX1 were also found to be associated with BD in our analysis as well as other GWAS studies 69,70 . ADCY1 plays a potential role in learning and memory 71,72 , whereas NPTX1 is required for neural cell speci cation and is also known to be involved in synaptic plasticity 73,74 .…”
Section: Discussionmentioning
confidence: 99%
“…Another ADCY family member, ADCY1 (adenylate cyclase 1), is the causative gene for human non-syndromic recessive hearing loss, DFNB44 [ 61 ]. In zebrafish, the Adcy1 mutants exhibited hair cell dysfunction [ 61 ], and ADCY1 and ADCY3 are classified into the same group based on their signaling properties [ 62 ]. Although phenotypes associated with hearing have not been reported in humans and mice, we might be able to study the amino acid substitution of ADCY3 as a candidate for ARHL resistance at the ahl10 locus.…”
Section: Discussionmentioning
confidence: 99%
“…ASD and RTT share some commonalities with RTT individuals showing some ASD-like behaviours [39,40]. ADCY7 mRNA is highly expressed in microglia and plays an important role in presynaptic GABA release and evidence suggests that ADCY7 is involved in mood regulation and plays an essential role in the immune response [41]. Conversely, despite ADCY9 being highly expressed in the brain, its function in the CNS remains largely unknown, however some findings have suggested that ADCY9 may regulate cognitive function and learning and memory [41].…”
Section: Meta-analysis Hub Genes Within the Skyblue Module Are Releva...mentioning
confidence: 99%
“…ADCY7 mRNA is highly expressed in microglia and plays an important role in presynaptic GABA release and evidence suggests that ADCY7 is involved in mood regulation and plays an essential role in the immune response [41]. Conversely, despite ADCY9 being highly expressed in the brain, its function in the CNS remains largely unknown, however some findings have suggested that ADCY9 may regulate cognitive function and learning and memory [41]. Interestingly, ADCY9 has been shown to be downregulated in Mecp2 null embryonic cortexes, suggesting ADCY9 as a target of MeCP2 [42].…”
Section: Meta-analysis Hub Genes Within the Skyblue Module Are Releva...mentioning
confidence: 99%
See 1 more Smart Citation